Comparing the safety and immunogenicity of a candidate TB vaccine MVA85A administered by intramuscular and intradermal delivery - Meyer, J; Harris, SA; Satti, I; Poulton, I; Poyntz, H; Tanner, R; Rowland, R; Griffiths, K; Fletcher, H; McShane, H (2013)
Background: New vaccines to prevent tuberculosis are urgently needed. MVA85A is a novel viral vector TB vaccine candidate designed to boost BCG-induced immunity when delivered intradermally. To date, intramuscular delivery has not been evaluated. Skin and muscle have distinct anatomical and immunological properties which could impact upon vaccine-mediated cellular immunity. Methods: We conducted a randomised phase I trial comparing the safety and immunogenicity of 1×108pfu MVA85A delivered intramuscularly or intradermally to 24 healthy BCG-vaccinated adults. Results: Intramuscular and intradermal MVA85A were well tolerated. Intradermally-vaccinated subjects experienced significantly more local adverse events than intramuscularly-vaccinated subjects, with no difference in systemic adverse events. Both routes generated strong and sustained Ag85A-specific IFNγ T cell responses and induced multifunctional CD4+ T cells. The frequencies of CD4+ T cells expressing chemokine receptors CCR4, CCR6, CCR7 and CXCR3 induced by vaccination was similar between routes. Conclusions: In this phase I trial the intramuscular delivery of MVA85A was well tolerated and induced strong, durable cellular immune responses in healthy BCG vaccinated adults, comparable to intradermal delivery. These findings are important for TB vaccine development and are of relevance to HIV, malaria, influenza and other intracellular pathogens for which T cell-inducing MVA-based vaccine platforms are being evaluated. © 2012 Elsevier Ltd.